Tobacco smoking and smoking cessation in times of COVID-19 - Elling, Jan M. (Tob Prev Cessat, 2020)
INTRODUCTION: Tobacco smoking may increase susceptibility to and severity of coronavirus disease 2019 (COVID-19). This information may influence smoking cessation related beliefs in smokers. METHODS: Online questionnaires were answered from 26 March to 3 April 2020 in the Netherlands by 340 smokers willing to quit smoking. Beliefs regarding (quitting) smoking and (consequences of) the coronavirus are described and associations with motivation to quit due to the coronavirus are reported. RESULTS: While 67.7% of the smokers indicated that the coronavirus did not influence the number of cigarettes smoked per day, 18.5% smoked less cigarettes and 13.8% smoked more cigarettes per day due to the coronavirus. One-third of the smokers were more motivated to quit smoking due to the coronavirus. Motivation to quit due to the coronavirus was positively associated with beliefs about the coronavirus as a serious threat, being at high risk of catching the coronavirus and developing severe illness, smokers being at higher risk than non-smokers, quitting smoking to reduce complaints, the social environment endorsing quitting, and perceived stress. CONCLUSIONS: Subgroups of smokers may be receptive to smoking cessation advice due to COVID-19. Because of the measures taken to reduce the spread of the virus (e.g. stay at home as much as possible), personalized digital health interventions may be particularly suitable to reach smokers at home.